The Power of Sequence: A Qualitative Analysis of Consumer Targeting and Spillover Effects in Social Media Advertising - Eka Wahyu Kasih; Benardi Benardi; Ruslaini Ruslaini (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative literature review titled "The Power of Sequence: A Qualitative Analysis of Consumer Targeting and Spillover Effects in Social Media Advertising" investigates the strategic interplay between consumer targeting, the sequencing of advertisements, and the resultant spillover effects within social media marketing. As social media platforms like Facebook and Twitter continue to evolve as vital advertising channels, understanding how to optimize consumer engagement through targeted strategies is essential for brands aiming to maximize their advertising returns. This review synthesizes existing literature on consumer behavior, advertisement sequencing, and information diffusion to establish a comprehensive framework for enhancing the effectiveness of social media campaigns. Findings indicate that strategic sequencing of advertisements can significantly enhance click-through rates and conversions by leveraging positive spillover effects. Moreover, the review identifies best practices for targeting specific demographic groups and suggests that an optimal sequence can lead to substantial budget savings in advertising expenditures. This study contributes valuable insights for marketers seeking to refine their social media advertising strategies and improve overall campaign performance, paving the way for future research in this rapidly evolving field.